Late Holocene environmental history of Northland, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Geography at Massey University, New Zealand - Striewski, Bernd; Striewski, Bernd (Massey University, 1999)
This thesis describes the environmental changes inferred from sedimentological investigations of sediment sequences at three lowland swamp and lake sites of Late Holocene age in Northland, northern North Island. The sites investigated are Wharau Road Swamp (coastal Bay of Islands), Lake Tauanui (inland Bay of Islands) and Lake Taumatawhana (central Aupouri Peninsula). The purpose of this sediment-based study was to reconstruct aspects of the environmental histories at these localities which would reflect the different environmental changes, natural and anthropogenic, that the sites proper and their drainage basins underwent through the passage of time. Particular emphasis was placed on human-induced environmental changes in order to address the on-going debate over the date of arrival of people in New Zealand. To this end the sediment sequences collected from the drainage basins of the above sites were analysed for a number of sedimentary parameters, including texture, sediment chemistry, mineralogy and organic matter content. In order to distinguish between natural and anthropogenic disturbances the results of these analyses were compared against the results of pollen and charcoal counts performed on the same sediment sequences. Wherever significant breaks in the sedimentological and palynological record of the sediment sequences were encountered, (bulk) samples were submitted for radiocarbon dating to establish a chronology of environmental changes. At Wharau Road Swamp the radiocarbon chronology was enhanced by the occurrence of one macro-tephra layer within the sediment sequence. The establishment of a radiocarbon chronology finally allowed one to determine the onset of sedimentologically-palynologically-demonstrated anthropogenic catchment disturbance at the respective localities. At Wharau Road earliest human presence was dated to ca. 600 (uncalibrated) years B.P. (about A.D. 1350) and at Lake Taumatawhana at ca. 900 (uncalibrated) years B.P. (about A.D. 1050). At Lake Tauanui sedimentological and palynological evidence for the beginning of human activities provide different dates. While sedimentological data only supported a date of ca. 350 (uncalibrated) years B.P. (about A.D. 1600) for the onset of human-induced catchment disturbances, the pollen and charcoal record suggested that anthropogenic deforestation began at ca. 1100 years B.P. (about A.D. 850).
Content removed due to copyright restriction Elliot, M. B., Striewski, B., Flenley, J. R., Kirkman, J. H., & Sutton, D. G. (1997). A 4300 year palynological and sedimentological record of environmental change and human impact from wharau road swamp, northland, new zealand. Journal of the Royal Society of New Zealand, 27(4), 401-418. Elliot, M. B., Striewski, B., Flenley, J. R., & Sutton, D. G. (1995). Palynological and sedimentological evidence for a radiocarbon chronology of environmental change and polynesian deforestation from lakes taumatawhana, northland, new zealand. Radiocarbon, 37(3), 899-916.
Keywords: Northland swamps; Northland lakes; Sediment analysis; Environmental changes; Palaeoecology